Microwave Assisted Synthesis and Antibacterial Activity of Chalcone Derivatives - Yadav, Khushbu; Sharma, Abha; Srivastava, J.N. (Asian Journal of Chemistry, 2012)
Chalcone derivatives have been synthesized by equimolar reactions between substituted aldehydes and substituted acetophenones in basic medium by using conventional and microwave assisted technique. These compounds are characterized by FTIR and 1H NMR spectra. Before characterization purity of these compounds has been checked by thin-layer chromatography method. These synthesized compounds have been screened for their antibacterial (E. coli, S. aureus) activities in different concentrations. The results showed that the chalcone derivatives are better at inhibiting growth of both types of bacteria (Gram negative and Gram positive) compared to chloramphenicol.